Suggested Rules of Origin Regime for EAFTA - Erlinda M. Medalla; M. Supperamaniam (Philippine Institute for Development Studies (PIDS), 2008)
In moving toward the East Asian vision of a community, a rational, enabling regime of rules of origin (ROOs) that would encourage deeper economic integration and shared prosperity should be established. This means a set of ROOs that is trade facilitating even as it attempts to prevent trade deflection, with enough safeguards for inclusive development both within and across countries in the region. To provide a clear understanding of the ROO and their proper application, this paper discusses the various approaches in determining the rules of origin. It also looks at the different ROO regimes in East Asia then points out some of the recurring ROO issues. Finally, the paper suggests key features of the ROO for the effective implementation and success of any preferential agreement such as the EAFTA.
Keywords: 330; rules of origin; regional trade agreement; preferential trading arrangements (PTAs); East Asia; free trade agreements (FTAs); Herkunftsbezeichnung; Handelspräferenzen; Regionale Wirtschaftsintegration; Freihandelszone; Ostasien